1997
DOI: 10.1016/s0009-9236(97)90156-9
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variations in serum levels and the renal toxicity of aminoglycosides in patients

Abstract: Animals show a faster clearance and a lower incidence of nephrotoxicity and ototoxicity when aminoglycosides are administered during the activity period. Human data on a circadian rhythm in pharmacokinetics are conflicting, and there are no data on a circadian rhythm in toxicity. When aminoglycosides are administered once daily, as is often done, a circadian rhythm in pharmacokinetics or toxicity could have clinical implications. In a prospective study we investigated the influence of drug administration time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 23 publications
2
42
0
4
Order By: Relevance
“…This was proven in a study involving 179 patients with severe infections treated with gentamicin or tobramicin. The nephrotoxicity was 34.6% during periods of resting (midnight to 7:30 a.m.) against 12.5% (8:00 a.m. to 3:30 p.m.) and 9.3% (4:00 p.m. to 11:30 p.m.) during active periods [50]. This variation is related to alterations in urinary pH, as there is greater interaction of aminoglycosides and anionic phospholipids when the pH is low [78].…”
Section: Clinical Trialsmentioning
confidence: 94%
See 1 more Smart Citation
“…This was proven in a study involving 179 patients with severe infections treated with gentamicin or tobramicin. The nephrotoxicity was 34.6% during periods of resting (midnight to 7:30 a.m.) against 12.5% (8:00 a.m. to 3:30 p.m.) and 9.3% (4:00 p.m. to 11:30 p.m.) during active periods [50]. This variation is related to alterations in urinary pH, as there is greater interaction of aminoglycosides and anionic phospholipids when the pH is low [78].…”
Section: Clinical Trialsmentioning
confidence: 94%
“…Among the factors related to patients are advanced age [46], preexistent renal disease [47], hypotension, volume depletion and hepatic dysfunction [48,49]. Factors related to aminoglycoside are high doses [2], the use of the drug for more than three days [2], reduction in the interval between doses [2], recent use of aminoglycosides and the administration of the drug between midnight and 7 o'clock a.m. [50]. The concomitant use of vancomycin, amphotericin B, furosemid, clindamycin, piperacilin, cephalosporin, foscarnet and the use of iodine contrast are also clinically associated with greater nephrotoxicity [2].…”
Section: Risk Factorsmentioning
confidence: 99%
“…17,18 Com relação às características clínicas, a maioria dos casos de IRA nefrotóxica isolada é não oligúrica (42%), porém, quando relacionada a outras causas, a prevalência de oligúria aumenta. 19,20 Em nosso estudo, 35,8% do total de pacientes com IRA nefrotóxica isolada eram oligúricos, comparados a 40,2% daquela relacionada a outras causas. A indicação dialítica mais frequente foi hipervolemia, em consonância com a maioria dos estudos.…”
Section: Tabelaunclassified
“…25 Alguns fatores aumentam a ocorrência de nefrotoxicidade por aminoglicosídeos, como uso de doses elevadas, uso da droga por mais de três dias, diminuição do intervalo das doses, uso recente de aminoglicosídeos e administração da droga no período das 24h às 7h. 19,20 Em nosso estudo, 12% apresentaram IRA nefrotóxica isolada.…”
Section: Tabelaunclassified
“…Numerous studies have suggested that the disposition and biologic effects of drugs can vary depending on the time of day [1][2][3]. Diurnal variations in steady-state concentrations have been observed for aminoglycosides [4], chemotherapeutic agents [5], and several anticonvulsants including carbamazepine [6], phenytoin [7], and ethosuximide [8].…”
Section: Introductionmentioning
confidence: 99%